2003
DOI: 10.1001/archopht.121.8.1151
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Statin Use to the 5-Year Incidence and Progression of Age-Related Maculopathy

Abstract: To examine the association of hydroxymethyl glutaryl coenzyme A reductase inhibitors (statins) with the 5-year incidence of age-related maculopathy (ARM). Design: Population-based cohort study. Participants included persons 48 to 91 years old examined March 1, 1993, through June 14, 1995, living in Beaver Dam, Wis (N=3684), of whom 2780 participated in a follow-up 5 years later. Methods: Standardized procedures were used for physical examinations, blood sample collection, and questionnaire administration. Age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…The Rotterdam and several other studies did not find a relationship between cholesterol-lowering medication [30][31][32] including statins [33] and risk of AMD. McGwin Jr. et al [34] evaluated the association between the use of cholesterol-lowering medications and AMD in the Atherosclerosis Risk in Communities (ARIC) study, a large, prospective, population-based cohort study conducted in four communities across the United States.…”
Section: Lipids and Amdmentioning
confidence: 77%
See 1 more Smart Citation
“…The Rotterdam and several other studies did not find a relationship between cholesterol-lowering medication [30][31][32] including statins [33] and risk of AMD. McGwin Jr. et al [34] evaluated the association between the use of cholesterol-lowering medications and AMD in the Atherosclerosis Risk in Communities (ARIC) study, a large, prospective, population-based cohort study conducted in four communities across the United States.…”
Section: Lipids and Amdmentioning
confidence: 77%
“…The association between the use of cholesterol-lowering medications, including statins, and AMD has also been intensively studied, but results are inconsistent [30][31][32][33][34][35][36][37]. The Rotterdam and several other studies did not find a relationship between cholesterol-lowering medication [30][31][32] including statins [33] and risk of AMD.…”
Section: Lipids and Amdmentioning
confidence: 99%
“…Most of studies are case-control and population-based Table 5 Studies' distribution of statins intake and age-related macular degeneration from 1991 to 2012 and their respective type, number of participants, and conclusion cohorts. 9,10,14,[23][24][25][26][27][28][29][30][31][32][33] There are four randomized clinical trials (RCTs), which evaluated the use of statins and AMD. 27,[34][35][36] The first RCT by Martini et al 36 and two other recent RCTs 27,34 that evaluated statin use and AMD did not find a significant protective association with AMD development.…”
Section: Resultsmentioning
confidence: 99%
“…Data from large population-based studies, including previous analyses from the Blue Mountains and Beaver Dam studies, have not found a protective association between statin use and ARMD (Klein et al, 2003). Some workers also stated that statin use is not reducing the risk for wet ARMD (van Leeuwen et al, 2004;Kaiserman et al, 2009).…”
Section: Statins and Incidence Of Age-related Macular Degenerationmentioning
confidence: 98%
“…The general consensus remains that a randomised trial of statin use in ARMD patients is warranted (Klein et al, 2003;McGwin et al, 2003;2005;Wilson et al, 2004;Chuo et al, 2007;Wong and Rogers, 2007). Wong and Rogers (2007) also proposed the initiation of a randomised controlled trial.…”
Section: Statins In the Treatment Of Age-related Macular Degenerationmentioning
confidence: 99%